Edukasi Pencegahan Stunting Melalui Pendidikan Keluarga di Desa Kuning II Kabupaten Aceh Tenggara - Nursafiah, Nursafiah; Maulina, Meutia; Nurlaila, Nurlaila; Maufira, Rila; Arivatussaqdiyah, Arivatussaqdiyah; Putri, Rahayu; Silvini, Yaumil; Hartono, Makmur; Suriani, Halisah; Yassir, Muhammad; Altin, Yunita; Ladipin, Ladipin; Akram, Habibul; Sukma, Mairi; Kurniawati, Kurniawati (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
Indonesia is a middle economic country that has nutritional health problems with a fairly high prevalence in Asia. In Kuning II Village, Bambel District, Southeast Aceh Tenggara, stunting is still relatively common. Stunting is a condition that describes chronic malnutrition status during a child's growth and development. Stunting is important to handle because it concerns the quality of human resources. Stunting can also occur before birth and is caused by very poor nutritional intake during pregnancy, very poor parenting patterns, and low quality food.   Stunting Apart from that, society is not yet aware of stunted children as a problem, because stunted children in society are seen as children with normal activities. By looking at the problem, this program aims to provide information and knowledge to the community so they can prevent and overcome the problem of stunting. The results achieved in this activity are that participants have knowledge about: the meaning of stunting and its characteristics, the causes and impacts of stunting, and how to overcome it.